2005
DOI: 10.4103/0253-7613.16215
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity of Pfaffia glomerata (Spreng.) Pederson (Amaranthaceae)

Abstract: Objective: To evaluate the free radical scavenging and cytotoxic activities of the butanolic (BuOH) extract, methanolic (MeOH) extract and 20-hydroxyecdysone extracted from the roots of Pfaffia glomerata. Materials and methods: Pfaffia glomerata roots were collected, powdered and extracted with methanol by maceration at room temperature. The extract was concentrated under vacuum, yielding a residue, followed by a butanol extraction. The 20-hydroxyecdysone (EC) was obtained by chromatographic separation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Several pharmaceutical manufacturers have produced phytopharmaceuticals containing P. glomerata , although only the roots have been processed to obtain the active ingredients [3,4]. The extracts show several biological properties including, gastroprotective effects [5], antioxidant activity [6,7], leishmanicidal potential [8], anti-inflammatory activity, and analgesic effect [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pharmaceutical manufacturers have produced phytopharmaceuticals containing P. glomerata , although only the roots have been processed to obtain the active ingredients [3,4]. The extracts show several biological properties including, gastroprotective effects [5], antioxidant activity [6,7], leishmanicidal potential [8], anti-inflammatory activity, and analgesic effect [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have confirmed the presence of significant amounts β-ecdysone in all of the major parts of P. glomerata , including stems and inflorescences [3,13]. Many pharmacological effects are attributed to β-ecdysone, such as antioxidant activity, and wound-healing and skin-regenerating properties, in addition to its use in cosmetic preparations [6,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The extract of Pfaffia glomerata roots has shown several biological properties, such as gastroprotective effects (FREITAS et al, 2004), leishmanicidal potential (TULMANN NETO et al, 2005), antiinflammatory activity, and analgesic effect (TULMANN NETO et al, 2004). Moreover, studies have reported that the extract of Pfaffia glomerata roots has antioxidant activity (DANIEL et al, 2005;LEAL et al, 2010;BATISTA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…β-ecdysone is a secondary metabolite with biotechnological, pharmacological, medical, and agrochemical applicability (FELIPE et al, 2019). Researchers have reported the antioxidant activity of this compound (DANIEL et al, 2005;LAFONT & DINAN, 2003;BATISTA et al, 2019). NSIMBA et al, (2008) showed that all of the isolated ecdysteroids in their study, including β-ecdysone, inhibited collagenase and the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation